A Software Products Line as Educational Tool to Learn Industrial Robots Programming with Arduino - Solis Pino, Andrés Felipe; Ruiz, Pablo H.; Hurtado Alegria, Julio Ariel (Electronics (Basel), 2022)
Software reuse has potential for educational purposes since it uses decomposition and abstraction, two necessary skills to learn programming. Software reuse techniques require abstractions that are not obvious to students or even to professionals. Taking advantage of these techniques, students can learn computer programming in a productive and organized way. This paper proposes to use the Software Product Line (SPL) reuse technique as a strategy for learning to program industrial robots with the Arduino platform. First, the paper explains SPL construction and application with first-year university students. The SPL proposes abstractions close to the industrial robots domain with a simplified variability. The paper uses the case study method to show the feasibility of using the SPL approach in a learning environment. In this evaluation, students reused 38% to 43% of the total code needed to program the robot. It represents an improvement in the time it takes students to program industrial robotics solutions facilitating their learning. In addition, the paper unveils some limitations related to usability, specific knowledge, and some exploitable technologies.